Genetics and molecular mapping for salinity stress tolerance at seedling stage in lentil (Lens culinaris Medik). Issue 3 (6th April 2020) - Singh, Dharmendra; Singh, Chandan Kumar; Tomar, Ram Sewak Singh; Sharma, Shristi; Karwa, Sourabh; Pal, Madan; Singh, Vijayata; Sanwal, Satish Kumar; Sharma, PC
Abstract: An investigation was conducted to understand the genetics and molecular mapping for salinity stress tolerance in lentil at the seedling stage. The populations were developed through crossing between salt sensitive (L‐4147 and L‐4076) and salt‐tolerant (PDL‐1 and PSL‐9) genotypes. The parents, F1, F2, F3 and backcross populations were assayed in salt solution at 120 mM NaCl for assessing salinity stress tolerance based on seedling survival and a Fluorescein diacetate (FDA) signal. The F1s were found tolerant to salinity stress indicating their dominance over the sensitive ones. The F2 segregation fitted well with the expected monogenic frequency ratio of salt‐tolerant: salt‐sensitive plants, which indicates that salinity stress tolerance is governed by a single dominant gene. This was also confirmed in F3 and backcross segregation data. Allelism test supported the hypothesis that the same gene was conferring stress tolerance in tolerant genotypes (PDL‐1 and PSL‐9). This matched with major QTL of seedling survival under salinity stress. Four hundred and ninety‐five SSR markers were analyzed for polymorphism and 11 of them were found polymorphic between the parents. Among eleven polymorphic markers, seven were associated with seedling survival under salinity stress. The QTL of this trait was mapped within a map distance of 133.02 cM in F2 mapping population (L‐4147 × PDL‐1) and it was found located on linkage group 1 (LG_1) and explained phenotypic variance of 65.6%. This report on QTL mapping should be useful for dissection of candidate genes and development of molecular markers for improvement of salinity stress tolerance in lentil.